Uji Aktivitas Antibakteri Kombinasi Ekstrak Etanolik Bawang Putih (Allium sativum L.) Dan Daun Alpukat (Persea Americana Mill.) Terhadap Pertumbuhan Bakteri Escherichia coli - Vicko Suswidiantoro; Mida Pratiwi; Riza Dwiningrum; Haikal Nur Islam; Eka Selviyana; Annisa Zahra; M.Syarif Alhauri; Anggun Fitria; Salsa della ananta putri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Garlic (Allium sativum L.) and Avocado Leaves (Persea Americana M.) are plants that have antibacterial activity due to the presence of secondary metabolite compounds. The aim of this study is to determine the antibacterial activity of the combination extract of Garlic and Avocado Leaves against Escherichia coli bacteria and to identify the groups of active compounds contained in the extracts of Garlic and Avocado Leaves. Antibacterial activity testing was carried out using the disk diffusion method. Garlic and Avocado Leaves were extracted using 96% ethanol solvent through the maceration method. The formula for the combination extract of Garlic and Avocado Leaves was in the concentrations of 25%:75%, 50%:50%, and 75%:25%. Identification of secondary metabolite compounds was conducted using reagents. The results showed that the extract of Garlic at a concentration of 50%:50% has the activity to inhibit Escherichia coli bacteria with the largest inhibition zone diameter of 18.91 mm, categorized as strong. Identification of secondary metabolite compounds with garlic extract and avocado leaves tested positive for alkaloids, flavonoids, saponins, and tannins. The conclusion of this study is that the best combination of extracts is found in garlic extract and avocado leaves, with an inhibition zone diameter of 18.91 mm, which falls into the strong category. Both garlic extract and avocado leaves have a significant influence on the inhibition zone diameter produced by the combined extract.